Conceptual Development and Evaluation of Heat Relief Principles for the Application in Bicycle Helmets. (2016) - Passler, Stefanie; Mitternacht, Jürgen; Janta, Marius; Senner, Veit
Abstract: The head is one of the most heat sensitive parts of the human body. In various sports head protection is obligatory resulting in a dilemma. In situations of high metabolism heat is accumulated due to insulation properties of the helmet, leading to enormous heat stress and discomfort. Today one way to improve heat dissipation from the head is via ventilation openings. But thermodynamically, further opportunities exist either active or passive. In this paper one material- and one technology-based concept are presented and evaluated with a physical thermal head model. The former uses evaporative cooling (convection). It consists of a water reservoir, a small pump to transport the water beneath the helmet, tubes and a textile for a homogeneous water distribution. The second uses materials with beneficial conductive properties (conduction) in direct contact to the head. This concept is realized by the use of heat pipes that are integrated in the structure of the helmet and a heat sink. Cooling effect of the concepts is evaluated in two controlled thermal environments (T1 =15°C; T2 =28°C; RH=70%). Thereby the head is heated up to a constant inner temperature of Thy =39°C that arises during high activity. The surface temperatures on the head are recorded by 61 evenly distributed temperature sensors, representing skin temperatures. Finally, cooling effect results from the heating energy that is needed to keep a constant core temperature. The analysed data relating to the required heating energy shows no differences between the HRSs and compared to the reference measurement. In contrast, a considerable effect of HRSs is determined, locally. Applying the HRS Heat pipe & Heat sink skin temperatures show decreases both at 15°C and at 28°C compared to the reference measurement. At sensor position 3 the maximum decrease can be seen by 25%. By using the HRS H 2 O at sensor position 3 skin temperature decreases by 13% at 15°C and by 8% at 28°C in comparison to the values of the reference measurement. Concerning the cooling effect, the comparison of both of the HRSs shows up to 17% better values at 15°C using the HRS Heat pipe & Heat sink . At 28°C no differences can be seen. Concerning the cooling effect and the disadvantages of the evaporative cooling principle, the HRS Heat Pipe & Heat sink is more suited for such an application in bicycle helmets. For applying this HRS to a bicycle helmet it has to be adapted to the entire helmet and to its shape.